Pumping of concrete: Understanding a common placement method with lots of challenges. (April 2022) - Feys, Dimitri; De Schutter, Geert; Fataei, Shirin; Martys, Nicos S.; Mechtcherine, Viktor
Abstract: Several million cubic meters of concrete are pumped daily, as this technique permits fast concrete placement. Fundamental research has been performed and practical guidelines have been developed to increase the knowledge of concrete behavior in pipes. However, the pumping process and concrete behavior are not fully understood. This paper gives an overview of the current knowledge of concrete pumping. At first, the known physics governing the flow of concrete in pipes are introduced. A series of experimental techniques characterizing concrete flow behavior near a smooth wall to predict pressure-flow rate relationships are discussed, followed by recent developments in the use of numerical simulations of concrete behavior in pipes. The influence of the pumping process on concrete rheology and air-void system is reviewed, and the first developments in active rheology control for concrete pumping are introduced. The last section of this paper gives an overview of open research questions and challenges.